'I believe high blood pressure can kill me:' using the PEN-3 Cultural Model to understand patients' perceptions of an intervention to control hypertension in Ghana. Issue 3 (3rd April 2019) - Blackstone, Sarah; Iwelunmor, Juliet; Plange-Rhule, Jacob; Gyamfi, Joyce; Quakyi, Nana kofi; Ntim, Micheal; Addison, Abigail; Ogedegbe, Gbenga
ABSTRACT: Objectives: Currently in Ghana, there is an on-going task-shifting strategy in which nurses are trained in hypertension management. While this study will provide useful information on the viability of this approach, it is not clear how patients in the intervention perceive hypertension, the task-shifting strategy, and its effects on blood pressure management. The objective of this paper is to examine patients' perceptions of hypertension and hypertension management in the context of an on-going task-shifting intervention to manage blood pressure control in Ghana. Design: Forty-two patients participating in the Task Shifting Strategy for Hypertension program (23 males, 19 females, and mean age 61. 7 years) completed in-depth, qualitative interviews. Interviews were transcribed, and key words and phrases were extracted and coded using the PEN-3 Cultural Model as a guide through open and axial coding techniques, thus allowing rich exploration of the data. Results: Emergent themes included patients' perceptions of hypertension, which encompassed misperceptions of hypertension and blood pressure control. Additional themes included enablers and barriers to hypertension management, and how the intervention nurtured lifestyle change associated with blood pressure control. Primary enabling factors included the supportive nature of TASSH nurses, while notable barriers were financial constraints and difficulty accessing medication. Nurturing factors included the motivational interviewing and patient counseling which instilled confidence in the patients that they could make lasting behavior changes. Conclusions: This study offers a unique perspective of blood pressure control by examining how patients view an on-going task-shifting initiative for hypertension management. The results of this study shed light on factors that can help and hinder individuals in low-resource settings with long-term blood pressure management.